SN 2020cpg: an energetic link between Type IIb and Ib supernovae. Issue 2 (22nd June 2021) - Medler, K; Mazzali, P A; Teffs, J; Prentice, S J; Ashall, C; Amenouche, M; Anderson, J P; Burke, J; Chen, T W; Galbany, L; Gromadzki, M; Gutiérrez, C P; et al.
ABSTRACT: Stripped-envelope supernovae (SE-SNe) show a wide variety of photometric and spectroscopic properties. This is due to the different potential formation channels and the stripping mechanism that allows for a large diversity within the progenitors outer envelope compositions. Here, the photometric and spectroscopic observations of SN 2020cpg covering ∼130 d from the explosion date are presented. SN 2020cpg ( z = 0.037) is a bright SE-SNe with the B -band peaking at MB = −17.75 ± 0.39 mag and a maximum pseudo-bolometric luminosity of L max = 6.03 ± 0.01 × 10 42 erg s −1 . Spectroscopically, SN 2020cpg displays a weak high- and low-velocity H α feature during the photospheric phase of its evolution, suggesting that it contained a detached hydrogen envelope prior to explosion. From comparisons with spectral models, the mass of hydrogen within the outer envelope was constrained to be ∼0.1 M⊙ . From the pseudo-bolometric light curve of SN 2020cpg a 56 Ni mass of M Ni ∼ 0.27 ± 0.08 M⊙ was determined using an Arnett-like model. The ejecta mass and kinetic energy of SN 2020cpg were determined using an alternative method that compares the light curve of SN 2020cpg and several modelled SE-SNe, resulting in an ejecta mass of M ejc ∼ 5.5 ± 2.0 M⊙ and a kinetic energy of E K ∼ 9.0 ± 3.0 × 10 51 erg. The ejected mass indicates a progenitor mass of 18−25 M⊙ . The use of the comparative light curve method provides an alternative process to the commonly used Arnett-like model to determine the physical properties of SE-SNe.